GENERAL DISTRIBUTION OF MOTOR CAPACITY FOR MIDDLE SCHOOL STUDENTS LOCATED AT DIFFERENT FLOOR ALTITUDE FROM WESTERN MOLDAVIA - Onose Ionut; Petrea Renato Gabriel (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The influence of the environment on physical activity of the individual is the focus of a research report from March 2011, conducted by experts from a Institution from that is responsible for monitoring obesity - National Obesity Observatory. The main result is that the environment influences the individual's physical activity and indirectly its health. In order to conduct the study, we started from the assumption that the relief altitude affects different general motor ability on middle school students from Western Moldavia. After conducting tests and interpreting the results, it outlines specific characteristics of each floor altitude, considering that coaches can choose large prospective athletes.